Vascular Endothelial Growth Factor and Cutaneous Scarring - Wilgus, Traci A. (Adv Wound Care (New Rochelle), 2019)
Significance: The proangiogenic mediator vascular endothelial growth factor (VEGF) plays an important role in cutaneous wound repair. Most of the work on VEGF and wound healing has focused on its role in mediating angiogenesis and how this affects wound closure rates. Less is known about how VEGF affects other phases of wound healing, including scar formation. Recent Advances: Over the last 10 years, mounting evidence suggests that VEGF plays an important role in regulating scar tissue production. Multiple studies have linked high VEGF levels with scar formation in normal, hypertrophic, and keloid scars. In addition, there is experimental evidence that VEGF inhibition can reduce scar tissue deposition. Critical Issues: While there is evidence that VEGF can promote scar formation in the skin, there are several unanswered questions that remain. First, the mechanisms by which VEGF promotes scar formation have not been completely characterized. While both indirect and direct mechanisms could be involved, clear evidence for a specific mechanism is lacking. In addition, despite the availability of anti-VEGF drugs, the potential value in targeting VEGF to attenuate scar formation clinically is not yet known. Future Directions: While there are a significant number of studies examining the effects of VEGF on angiogenesis and wound closure, much less attention has been paid to the contribution of VEGF to scar tissue production. Additional studies are required to learn more about how VEGF regulates scar formation and whether VEGF inhibition could be used clinically to manage scars.